Art Therapy sebagai Alat Pengelolaan Emosi: Sebuah Kajian Literatur - Andi Arjulia Sari (Jurnal Pendidikan Dasar dan Menengah (Dikdasmen), 2025)
This research has a descriptive aim to describe various art therapy models in managing emotions. This research uses a literature review method. The literature analysis and review process is assisted by a literature review table which contains the title, year, author, type of research or method used, research subject, mechanism for implementing the intervention (art therapy) and the results of previous research or research being studied. This research examines seven different literatures. In this research, the results obtained were several forms of applying art therapy that were effectively used for managing emotions based on the research studied, namely drawing, painting, drawing while singing, music, making collages, writing, and making animals from clay. This research has limitations because the literature used is still limited with a small number. More literature is needed to find references for forms of art therapy that can be effectively used as a medium for managing emotions.